EFFECT of GAMMA IRRADIATION on CAPROLACTAM MIGRATION FROM MULTILAYER POLYAMIDE 6 FILMS INTO WATER FOOD SIMULANT and VALIDATION of THE METHOD - Felix, J. S.; Manzoli, J. E.; Padula, M.; Monteiro, Magali [UNESP] (Chiriotti Editori, 2011)
A gas chromatographic method to determine caprolactam migration from non-irradiated and irradiated multilayer polyamide 6 films into water food simulant was developed and validated. Linear range was 0.96 to 642.82 mu g/mL, with correlation coefficient of 0.9999. Limit of detection and quantification was 0.32 and 0.96 mu g/mL, respectively. Method precision showed RSD values lower than 2.1%, while method accuracy showed recovery from 89 to 105%. Caprolactam levels reduced with the increase of radiation dose for films used for meat foodstuffs, while for films used as cheese packaging only slight differences occurred.
Keywords: caprolactam; migration; multilayer polyamide 6 films; gamma irradiation; validation of analytical method